Asymmetric synthesis using sugars as homochiral auxiliaries - Ab. Wahab, Roswanira (2006)
The development of the area of asymmetric synthesis has increased interests of many organic chemists. Asymmetric synthesis simply means the selective generation of new chirality elements by action of chiral reagents in which many are found naturally. In this study, the addition reaction of enones with N-bromosuccinimide (NBS) in series of primary alcohol was observed and produced bromoalkoxy adducts as major products as well as their diastereomers which made up the portion of the minor isomers. The major adducts were isolated by direct recrystallisation of the crude products. 2-Methyl-1- propanol and 1-propanol were found to demonstrate the highest selectivity in the addition reaction and gave diastereomic ratio of 15.3:1 and 13:1 respectively. The formation of the major adducts increases with increasing molecular weight of the alcohol. The bromoalkoxylation of the major adducts may be due to predominant formation of gauche conformation of the substituents on the two stereogenic centres. This may have contributed to the lower steric hindrance and a lower potential energy. The removal of the sugar auxiliary from the bromoalkoxy derivatives was successfully performed using trifluoreacetic acid and ethane-1,2-diol to yield mixtures of acetal and tetraacetylglucose. Trifluoroacetic acid was observed to be an excellent reagent in the removal of the sugar auxiliary. The tetraacetylglucose was removed from the acetal, by treatment with p-toluenesulphonic acid in methanol to produce pure acetal as a colourless oil. The bromoalkoxy adducts were characterized using infrared (IR) and nuclear magnetic resonance (1H-NMR) spectroscopies.